2007
DOI: 10.1183/09031936.00161906
|View full text |Cite
|
Sign up to set email alerts
|

Pharyngeal narrowing in end-stage renal disease: implications for obstructive sleep apnoea

Abstract: Sleep apnoea is common in patients with end-stage renal disease (ESRD). It was hypothesised that this is related to a narrower upper airway. Upper airway dimensions in patients with and without ESRD and sleep apnoea were compared, in order to determine whether upper airway changes associated with ESRD could contribute to the development of sleep apnoea.An acoustic reflection technique was used to estimate pharyngeal cross-sectional area. Sleep apnoea was assessed by overnight polysomnography. A total of 44 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
0
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 28 publications
5
50
0
6
Order By: Relevance
“…First, the upper airway dimensions in patients with renal failure are prone to narrowing. Beecroft et al reported that the pharyngeal cross-sectional area measured by pharyngometry in end-stage renal disease patients was 12% less than that in the normal renal function control group matched for BMI (25). They insisted that this difference was clinically significant because in another study as little as a 6% reduction in the pharyngeal crosssectional area led to a 73% increase in AHI (26).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…First, the upper airway dimensions in patients with renal failure are prone to narrowing. Beecroft et al reported that the pharyngeal cross-sectional area measured by pharyngometry in end-stage renal disease patients was 12% less than that in the normal renal function control group matched for BMI (25). They insisted that this difference was clinically significant because in another study as little as a 6% reduction in the pharyngeal crosssectional area led to a 73% increase in AHI (26).…”
Section: Discussionmentioning
confidence: 96%
“…They insisted that this difference was clinically significant because in another study as little as a 6% reduction in the pharyngeal crosssectional area led to a 73% increase in AHI (26). Such pharyngeal narrowing was considered to occur because of upper airway edema due to systemic fluid overload and upper airway dilator muscle dysfunction due to neuropathy or myopathy associated with chronic uremia (25). Second, ventilation control is known to be instable in CKD patients.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this notion, Chiu et al (18) recently applied lower body positive pressure using antishock trousers to displace fluid from the legs to the upper body, and found that the maneuver resulted in increased pharyngeal airflow resistance. Beecroft et al (19) recently showed that pharyngeal narrowing contributes to the pathogenesis of OSA in dialysis-dependent patients. Furthermore, in patients converted from conventional to nocturnal hemodialysis, there was an increase in pharyngeal size together with improvement in sleep apnea (20).…”
Section: Discussionmentioning
confidence: 99%
“…279 CKD may lead to sleep apnea by autonomic nerve damage, effected by generalized uremic neuropathy, interfering with baroreceptor activity, pharyngeal narrowing due to fluid overload, and accumulation of uremic toxins. [279][280][281][282][283][284] Sleep apnea likely causes CKD through numerous mechanisms that promote renal hypoxia. 285,286 The most obvious mechanism is that apnea causes insufficient or absent ventilation, compromised gas exchange, and, thus, intermittent nocturnal hypoxia.…”
Section: Repeated Episodes Of Acute Kidney Injurymentioning
confidence: 99%